Polypyrrole Composite Nanoparticles with Morphology‐Dependent Photothermal Effect and Immunological Responses. Issue 6 (23rd December 2015) - Tian, Ye; Zhang, Jianping; Tang, Shiwei; Zhou, Lei; Yang, Wuli
Abstract : Polypyrrole composite nanoparticles with controlled shape are synthesized, which exhibit a morphology‐dependent photothermal effect: the raspberry‐like composite nanoparticles have a much better photothermal effect than the spherical ones, and the immune responses to the nanocomposites are also dependent on their morphology. The outstanding performance of the nanocomposites promises their potential application in photothermal therapy and immunotherapy of cancer.